การศึกษาความเป็นไปได้ด้านการพาณิชย์และด้านกายภาพ ของการขุดคอคอดกระ ส่วนที่ 3 : ส่วนการศึกษาด้านสิ่งแวดล้อม : รายงานผลการวิจัย - เปี่ยมศักดิ์ เมนะเศวต (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The feasibility study on the Kra Canal : commercial and physical aspects for environmentl impact studied part was composed of project descriptive, area and condition, field survey and secondary data collection and impact assessment to interested parameter. The project used 5A line as model which open to Andaman Sea at Pak Bara District, Satun Province and open to the Gulf of Thialnd at Singhanakorn District, Sonkla Province. The distance on land was 102 kilometers and was 120 kilometers included coastal area. The expected constructionwas estimated for 500,000 dead weight tonnage with 2 canals, and for 250,000 dead weight tonnage with 1 canal. Impact assessment studied method combined Simple Checlist, Descriptive Checklist and Scaling Checklist method at Construction and Operation phase. The interesting paranmeter were Physical Parameter, Biological Parameter and Resources Utilization Parameter. For Andaman Sea the adverse impact level at 0, -1, -2 and -3 (from lowest to highest level) was found as 2, 2, 8 and 15 parameters from 32 parameters, and beneficail impact level at 1,2 1nd 3 (from lowest to highest level) was found as 1 and 4 parameters from 32 parameters. For the Gulf of Thailand the adverse impact level at 0, -1, -2 and -3 (from lowest to highest level) was found as 3, 4, 5 and 15 parameters from 32 parameters, and beneficial impact level at 1, 2 and 3 (from lowest to highest level) was found as 1 and 4 parameters from 32 parameters.